2020
DOI: 10.1097/mao.0000000000002694
|View full text |Cite
|
Sign up to set email alerts
|

Electrocochleography and Cochlear Implantation: A Systematic Review

Abstract: Objective: Given the heterogeneity of papers about electrocochleography (ECochG) and cochlear implantation (CI) and the absence of a systematic review in the current literature, the aim of this work was to analyze the uses of ECochG in the different stages of CI. Data Sources: A search of PubMed from inception to December 8, 2019, with cross-references, was executed. Keywords were: “Cochlear Implant” OR “Cochlear Implantation” AND “Electrocochleography”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 83 publications
1
12
0
1
Order By: Relevance
“…To further improve hearing preservation rates, a better understanding of the mechanisms leading to loss of residual hearing in CI recipients is deemed necessary. Previous studies have shown that intracochlear electrocochleography (ECochG) is a promising method to gather information about the status of cochlear structures during and after cochlear implantation (Trecca et al 2020). It has been used to monitor cochlear trauma during cochlear implantation (Giardina et al 2019; O’Leary et al 2020; Weder et al 2020; Bester et al 2021; Sijgers et al 2021; Weder et al 2021) and enhance the understanding of postoperative changes within the cochlea (Dalbert et al 2015; Bester et al 2017; Campbell et al 2017; Hoesli et al 2018; Bester et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…To further improve hearing preservation rates, a better understanding of the mechanisms leading to loss of residual hearing in CI recipients is deemed necessary. Previous studies have shown that intracochlear electrocochleography (ECochG) is a promising method to gather information about the status of cochlear structures during and after cochlear implantation (Trecca et al 2020). It has been used to monitor cochlear trauma during cochlear implantation (Giardina et al 2019; O’Leary et al 2020; Weder et al 2020; Bester et al 2021; Sijgers et al 2021; Weder et al 2021) and enhance the understanding of postoperative changes within the cochlea (Dalbert et al 2015; Bester et al 2017; Campbell et al 2017; Hoesli et al 2018; Bester et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Another exciting technique enabling intraoperative monitoring is electrocochleography. It provides additional information about cochlear and neural dysfunctions [39] and could help preserve residual hearing [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…ANSD can also be assessed by electrocochleography showing an absent or abnormal compound action potential, even at high stimulations, and the presence of a robust cochlear microphonic. A detailed diagnosis of the site-of-lesion is also fundamental for the prediction of CI outcomes, which are generally worse in neuropathic patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%